Sterols in asphalt roofing materials

By adding sterols to the oxidized asphalt adhesive of the roofing material, the problem of aging of the asphalt adhesive of the roofing material is solved, extending the service life and improving performance.

CN119775960APending Publication Date: 2025-04-08ALM HOLDING CO +1
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202411974831.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2020-05-20
Filing Date
2020-07-15
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The asphalt adhesive of existing roofing materials is prone to aging, resulting in reduced performance and difficult to meet the needs of long-term use.

Method used

Stearol is added to the oxidized asphalt binder composition to delay or slow down the aging rate and improve rheology performance.

Benefits of technology

By adding sterol, the service life of the roofing material can be extended, some or all of the original properties of the original bitumen binder can be maintained or restored, and the aging speed can be reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005220207540000111
    Figure BDA0005220207540000111
  • Figure BDA0005220207540000151
    Figure BDA0005220207540000151
  • Figure BDA0005220207540000161
    Figure BDA0005220207540000161
Patent Text Reader

Abstract

Compositions and methods of making and using asphalt roofing materials are disclosed. The asphalt roofing material includes sterols. The sterol improves various rheological and aging properties of the asphalt roofing material.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application claims the benefit of U.S. Provisional Patent Application Serial No. 62 / 874,229 filed on July 15, 2019, U.S. Provisional Patent Application Serial No. 62 / 887,811 filed on August 16, 2019, and U.S. Provisional Patent Application Serial No. 63 / 027,845 filed on May 20, 2020, the disclosures of which are incorporated herein by reference in their entirety. Background Art

[0002] Asphalt has been used in roofing materials such as roofing tiles, roll roofing, and built-up roofing. Typically, the roofing material includes a substrate such as fiberglass mat, an asphalt-based paint that impregnates the substrate and coats the top and bottom, and a granular layer embedded in the top paint. The asphalt paint typically contains fillers such as ground limestone. Roofing tiles may also have a dust backing material such as silica sand on the bottom paint to prevent the tiles from sticking together in bundles.

[0003] The composition used to make the roofing material determines to a large extent the properties of the resulting roofing material (eg, aging, cracking, blistering, algae resistance, flexibility, and adhesion).

[0004] There remains a need for roofing materials with improved aging characteristics. Summary of the invention

[0005] A composition and method are disclosed which can be used in asphalt-based coatings for roofing materials to retard, reduce or otherwise improve the aging rate of asphalt binders in such coatings and roofing materials. Also disclosed are roofing materials containing such compositions.

[0006] In one aspect, a method for retarding the aging rate of an asphalt-based roofing material or beneficially improving the rheological properties of an aged asphalt-based roofing material comprises adding a sterol to an oxidized asphalt binder composition, wherein the oxidized asphalt binder composition comprises virgin oxidized or air blown asphalt binder, aged oxidized or air blown asphalt binder, or both.

[0007] In another aspect, is a method of reusing aged asphalt binder from roofing materials, the method comprising treating the aged asphalt binder to provide an oxidized asphalt binder, and adding a sterol to the oxidized asphalt binder composition, wherein the asphalt binder composition comprises an asphalt binder extracted from the roofing material.

[0008] In another aspect, a method of making a roofing material comprises: treating an asphalt binder to provide an oxidized asphalt binder; adding a sterol to the oxidized asphalt binder composition to form a coating asphalt composition, wherein the coating asphalt composition comprises virgin oxidized or air blown asphalt binder, aged oxidized or air blown asphalt binder, or both; and coating the roofing material with the coating asphalt composition.

[0009] In other aspects, is a roofing material comprising a coated roofing substrate, wherein the coated roofing substrate includes a coating asphalt containing sterols and an asphalt binder, wherein the asphalt binder comprises virgin oxidized or air blown asphalt binder, aged oxidized or air blown asphalt binder, or both.

[0010] Sterols can be used to retard or slow the rate of aging, or to restore or renew aged oxidized or air-blown asphalt or aged oxidized or air-blown adhesive to provide some or all of the original properties of the original oxidized or air-blown asphalt or original adhesive to be used in roofing materials. Sterols can be added to the original or aged asphalt binder before or after oxidation or air blowing, or can be provided by recovering the sterols from an aged asphalt binder containing the sterols before aging. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] Figure 1 Graphically represents the temperature at which several recycled tile waste adhesives reach a stiffness of 1 kPa.

[0012] Figure 2 The Tm critical temperature of recycled tile waste binders with and without sterols under pressure aging vessel (PAV) aging conditions is graphically presented.

[0013] Figure 3 The rheological index, also known as the R-value, of recycled tile waste adhesives with and without sterols under PAV aging conditions is graphically presented.

[0014] Figure 4 Graphically represents the temperature at which the coating asphalt reaches a stiffness of 1 kPa.

[0015] Figure 5 The Tm critical temperature of coating asphalt with and without sterols is graphically represented.

[0016] Figure 6 Graphical representation of the asphaltene content of recycled shingle binders and paint asphalt binders under various aging conditions.

[0017] Figure 7 Graph showing the ΔTc versus PAV aging time for coating asphalts with and without sterols.

[0018] Figure 8 The rheological index (R-value) of the coating asphalt with and without sterols is graphically presented as a function of aging time.

[0019] Fig. 9 The rheological index (R-value) of the coating asphalt with and without sterols is graphically presented as a function of aging time.

[0020] Fig.10 A graphical representation of the comparison of the Tm critical temperature of unfilled coating asphalt and filled coating asphalt.

[0021] Fig.11 A comparison of the temperatures at which unfilled and filled coating pitches reach a stiffness of 1 kPa is graphically presented when the unfilled and filled coating pitches contain sterols at 0 wt.%, 5 wt.%, and 8 wt.% of the coating pitch sample.

[0022] Fig.12 Graph showing asphaltene concentration of aged non-air blown base binders containing various sterol loadings as a function of binder aging time in the PAV.

[0023] Fig.13 It is the Fourier transform infrared (FTIR) spectrum of pure phytosterols.

[0024] Fig.14 It is a zoomed-in view of the wavenumber region of interest for sterols.

[0025] Fig.15 It is a zoomed in view of the FTIR subtraction spectrum result of FTIR of 60 hours PAV with 5% sterol minus FTIR of 60 hours PAV without sterol.

[0026] Fig.16 Is a zoomed in view of the FTIR subtraction spectrum results of the FTIR of the 60 hour PAV of the 50 / 50 blend of 0% sterol and 10% sterol minus the FTIR of the 60 hour PAV without sterol.

[0027] Fig.17 is a graph of the FTIR subtraction spectrum results of the FTIR spectrum of the 60-hour PAV containing 10% sterols minus the FTIR spectrum of the 60-hour PAV without sterols. The graph shows that the 1145 to 943 cm- 1 The area of ​​the region is 0.1458.

[0028] Fig.18 Comparison of R-value and low temperature performance data for 50% aged adhesive mixed with 10% sterol vs. aged adhesive without sterol for 60 hour PAV samples.

[0029] Fig.19Comparison of high temperature PG ratings for 50% aged adhesive mixed with 10% sterols vs. aged adhesive without sterols for the 60 hour PAV samples.

[0030] Fig. 20 Black space plots for aged basal control with no additional aging and 60 hours PAV, 5% and 10% sterols at 60 hours PAV, and a 50 / 50 blend of basal aged with 10% sterols at 60 hours PAV.

[0031] Fig.21 It is a high temperature PG grade at 1 kPa stiffness.

[0032] Fig. 22 It is a high temperature PG grade at 2.2 kPa stiffness.

[0033] Fig.23 is a graph of the Tm thresholds for 0%, 6% and 12% sterols in PG 64-22 under unaged and 60 h PAV aged conditions.

[0034] Fig.24 is a graph of R values ​​for 0%, 6% and 12% sterols in PG 64-22 under unaged and 60 hour PAV aged conditions.

[0035] Fig.25 is a graph of the percentage of asphaltene as a function of age and sterol content.

[0036] Fig.26 is the Black space plot for all blends containing 0%, 6% and 12% sterols, aged and unaged.

[0037] Fig. 27 is a Black space plot highlighting that all blends containing 6% sterols follow the same Black space data trajectory: The other data show that the 0%, 6%, and 12% sterol blends follow different plot lines.

[0038] Fig.28 is a Black space plot highlighting that all blends containing 12% sterols follow the same Black space data trajectory: The other data show that the 0%, 6% and 12% sterol blends follow different plot lines.

[0039] Fig.29 IATROSCAN of unaged PG 64-22 and PG 64-22 aged for 60 hours in PAV TM Overlay of flame ionization detector (FID) spectra.

[0040] Fig.30This is the IATROSAN (FID) spectrum of 60-hour PAV PG 64-22 plus 12% sterols.

[0041] Fig.31 Overlaid IATROSCAN (FID) spectra of 64-22 + 12% sterols added after 60 hours PAV aging and PG 64-22 + 12% sterols followed by 60 hours PAV aging.

[0042] Fig.32 Overlaid IATROSCAN (FID) spectra of two test results of unaged PG 64-22 + 6% sterols, and PG 64-22 + 6% sterols then aged in PAV for 60 hours.

[0043] Fig.33 Overlaid IATROSCAN (FID) spectra of two tests of unaged PG 64-22 + 6% sterols, PG 64-22 + 6% sterols then aged in PAV for 60 hours, and a 50 / 50 blend of aged 64-22 0% sterols and 64-22 + 12% sterols aged for 60 hours. DETAILED DESCRIPTION

[0044] "Aged" refers to an asphalt binder that is brittle, has high stiffness, a high softening point, and has poor aged qualities relative to the original oxidized binder.

[0045] "Binder" refers to petroleum in a high viscosity liquid or semi-solid form. "Binder" may include, for example, asphalt. The term "bituminous binder" may be used interchangeably with the term "binder."

[0046] "Asphalt" refers to a class of black or dark-colored (solid, semisolid or viscous) cementitious materials that are natural or processed and are composed primarily of high molecular weight hydrocarbons, typical of which are asphalt, tar, pitch and asphaltenes.

[0047] "Crude" when used with respect to sterol-containing material refers to sterols that have not been fully refined and can also contain other components in addition to sterols.

[0048] The "m-critical" or "creep critical" rating refers to the low temperature relaxation rating of the paving adhesive. The creep critical temperature is the temperature at which the absolute value of the slope of the flexural creep stiffness versus creep time (per ASTM D6648 or AASHTO T31 or Bending Beam Rheometer (BBR) test) is 0.300. The creep critical temperature can also be determined by a 4 mm Dynamic Shear Rheometer (DSR) test with a value of -0.275.

[0049] "Neosterol" refers to sterol that has not been used in asphalt pavement or asphalt shingles or has not been regenerated from asphalt pavement or asphalt shingles.

[0050] "Neat" or "virgin" binder is a binder that has not been previously used in or recycled from asphalt pavement or asphalt shingles, which may include performance grade binders.

[0051] "PAV" refers to the Pressurized Aging Vessel test. The PAV test is used to simulate the accelerated aging of asphalt binders using a pressurized aging vessel as described in ASTM D6521-13 (Standard Practice for Accelerated Weathering of Asphalt Binders Using a Pressurized Aging Vessel (PAV)).

[0052] When used with respect to a sterol or sterol mixture, "pure" means at least technical grade purity or at least reagent grade purity.

[0053] “Recycled asphalt shingles” and “RAS” refer to asphalt binders that are recovered or extracted from used roofing materials, including manufacturer’s discards or production waste.

[0054] "Recycled sterols" refers to sterols contained in aged asphalt binder or binder previously present in existing, used asphalt pavement or existing, used or unused asphalt shingles.

[0055] "Roofing bituminous binder" or "coating bituminous binder" means a bituminous binder suitable for use in the manufacture of roofing materials as defined in ASTM D 3462: having a minimum softening point of 88°C (190°F) to 113°C (235°F) and a minimum penetration of 15 dmm at 25°C (77°F).

[0056] "Roofing filler" or "filler" refers to materials, such as minerals, used in the manufacture of asphalt roofing materials. The filler material is characterized by a particle size of 100-400 mesh and a range of 1-80 wt. % of the total roofing asphalt composition.

[0057] "Roofing granules" or "granules" refer to materials, such as minerals, that are applied to the top of roof tiles. The granules have a particle size of 8-40 mesh.

[0058] The term "roofing material" in the context of "asphalt roofing material" means materials containing an asphalt binder, including roofing tiles, roll roofing, built-up roofing, post-consumer waste (e.g., broken tiles) or manufacturer's discarded tiles, tile manufacturing waste, roofing felt, etc.

[0059] "S-critical" or "stiffness critical" rating refers to the low temperature stiffness rating of an adhesive. The stiffness critical temperature is the temperature at which the adhesive has a flexural creep stiffness value of 300 MPa when tested according to ASTM D6648 or as determined by a bending beam rheometer test (ASTM D6648 or AASHTO T313) or a 4 mm DSR test (described in ΔTc).

[0060] "Sterol" or "sterol additive" means one or more sterols or a combination thereof with a binder used to retard or slow the rate of aging of an asphalt binder (i.e., aged or original), or to restore or renew aged asphalt or aged binder to provide some or all of the original properties of the original oxidized asphalt or original oxidized binder.

[0061] "ΔTc" refers to the value obtained when the low temperature creep or m-value critical temperature is subtracted from the low temperature stiffness critical temperature. ΔTc can be measured by the bending beam rheometer test (ASTM D6648 or AASHTO T313) described above, or by a 4 mm dynamic shear rheometer (DSR) test as described by Sui et al. (2010), Sui et al. (2011), or Farrar et al. (2012) from Western Research Institute, described below.

[0062] "Upcycled asphalt binder" refers to an asphalt binder composition comprising a used asphalt binder containing recycled sterols. For asphalt binders containing sterols, upcycled may be used interchangeably with "recycled".

[0063] The use of numerical ranges using endpoints includes all numbers subsumed within that range (eg, 1 to 5 includes 1, 1.5, 2, 2.75, 3, 3.80, 4, and 5, etc.).

[0064] Unless otherwise indicated, all weights, parts and percentages are by weight.

[0065] The use of sterols in roofing materials is disclosed. Sterols have been shown to slow down the aging rate of oxidized roofing adhesives. Applicants have previously shown that sterols can delay, reduce or otherwise overcome some of the effects of asphalt aging, thereby maintaining or retaining some or all of the original properties of the original asphalt adhesive. See International Applications PCT / US16 / 037077, PCT / US16 / 64950 and PCT / US16 / 064961, PCT / US17 / 045887, each of which is incorporated herein by reference in its entirety. Sterols are used together with adhesives containing recycled or regenerated materials (e.g., recycled asphalt pavement (RAP), recycled asphalt shingles (RAS) or a combination of both and pavement aggregate).

[0066] RAS is an attractive component for recycling and reuse because of its high asphalt binder content. RAS, for example, may have an asphalt binder content in the range of 15% to 35%, compared to RAP, which may have an asphalt content of about 5%. Asphalt binder from newly manufactured shingles, for example, may have an asphalt binder content of about 20%.

[0067] A roofing material may be constructed using a felt (e.g., fiberglass felt), a coating based on an asphalt binder, and a granular layer embedded in an asphalt-based top coating. The felt is impregnated with hot saturated asphalt binder, followed by more asphalt binder on both sides, and finally the surface is covered with granular material. The saturant and coating asphalt binder do not have to be the same. The coating applied to the top covers the top of the felt, the felt partially saturates the felt, and the bottom covers the bottom of the felt. As used herein, "top" refers to the side facing up or away from the roof when the roofing material is installed on the roof, and "bottom" refers to the side facing down or toward the roof.

[0068] The felt may be of any type known for reinforcing roofing materials based on asphalt binders, such as a mesh, scrim or felt of fibrous material, such as a nonwoven felt of glass fibers, mineral fibers, cellulose fibers, rag fibers, synthetic fibers (e.g., polymer fibers), or mixtures thereof. In some embodiments, the felt is an organic felt made from cellulose fibers, or a glass felt made from glass fibers. In some embodiments, the roofing tiles produced are of the organic felt type.

[0069] In addition to the asphalt binder, roofing asphalt may contain other materials such as fillers, polymers, waxes, stabilizers, pigments, antioxidants, and / or solvents. Roofing tiles typically have a dust backing material (such as silica sand) on the base coating to prevent them from sticking together in clumps.

[0070] In some embodiments, the filler is about 1 wt % to 80 wt %, 45 wt % to 60 wt %, 50 wt % to 75 wt % or 60 wt % to 80 wt % of the weight of the coating. In some embodiments, the filler is a particle of a sedimentary rock or mineral (e.g., limestone or calcium carbonate, dolomite, silica, talc, shale, clay, mica or a combination thereof). Other suitable fillers include fly ash, carbon black and inorganic fibers or a combination thereof. In other embodiments, the filler is a sedimentary rock particle. The fillers used for the top, bottom or felt coatings do not have to be the same. In some embodiments, the filler is used to impart desired mechanical properties to the tile, to reduce raw material costs, or both.

[0071] The top surface of the coating asphalt binder of the roofing tile is coated or embedded with roofing granules. Roofing granules provide the desired weather resistance, fire resistance, visual decorative exterior surface or any combination thereof for various roof types. In some embodiments, the granules are crushed and sieved mineral materials, which are then coated with the coating asphalt binder. In some embodiments, the granules are hard mineral bedrock, such as slate, basalt or nepheline. In some embodiments, the granules are the same type of granules, or can be a mixture of granules of different types, textures, shapes and / or colors.

[0072] Asphalt binder compositions suitable for use in the manufacture of roofing materials, such as painted roofing tiles, are generally produced by selecting an appropriate asphalt binder (sometimes referred to as an asphalt flux) and treating the asphalt binder to obtain properties useful for roofing materials. For example, roofing asphalt binders generally retain a certain degree of hardness and do not flow under high temperature conditions. This increased hardness is generally accompanied by reduced penetration levels, increased viscosity, and increased softening point.

[0073] In some embodiments, the roofing asphalt binder is treated by air blowing, which is an oxidation process that involves blowing air through the molten asphalt binder to change the physical properties of the asphalt binder. In this process, air is blown through the asphalt binder at an elevated temperature for a period of time. The air blowing process generally increases the softening point of the asphalt binder, thereby increasing the ability of the roofing material (e.g., roofing tiles) to resist high temperature flow on the roof, reduces the penetration of the tiles without becoming too brittle, increases the melt viscosity so that when fillers are added, the filler coating viscosity is within a range that allows the roofing tiles to be effectively treated, and forms tiles that can withstand exposure to sunlight, high temperatures, and adverse weather conditions.

[0074] Specifications for roofing materials are listed in ASTM D255 ("Asphalt Binder Shingles with Mineral Aggregates on the Surface (Organic Felt)", American Society for Testing and Materials, Annual Book of ASTM Standards, Volume 04.04, West Conshohocken, Pennsylvania, 1996); and ASTM D3462 ("Asphalt Binder Shingles Made of Glass Felt and Surfaced with Mineral Aggregates", American Society for Testing and Materials, Annual Book of ASTM Standards, Volume 04.04, West Conshohocken, Pennsylvania, 1996).

[0075] The properties of the roofing asphalt binder composition can be measured by any suitable test known and accepted in the art. For example, asphalt binder properties are measured as follows: softening point or "SP" is measured by ASTM D36; needle penetration or "pen" is measured by ASTM D5 operated at 25°C; melt viscosity is measured by ASTM D4402 operated at 204°C (400°F) using an LV Brookfield type viscometer (using a No. 18 spindle, 6 RPM) or a RV Brookfield type viscometer (using a No. 21 spindle, 50 RPM); durability is measured by ASTM D4798; flash point is measured by ASTM D92; and stability is measured by ASTM D3791 modified to run at an oven temperature of 260°C (500°F) for up to 5 days or a similar test procedure.

[0076] In some embodiments, a method of preparing a coating asphalt binder composition comprises heating the asphalt binder to a temperature of about 49°C (120°F) to about 288°C (550°F) until the asphalt binder liquefies into a molten asphalt binder material. The molten asphalt binder may then be oxidized to adjust the properties of the molten asphalt binder, particularly to increase the softening point. Various methods of oxidizing the molten asphalt binder may be used, such as an "air blowing" process. The air blowing process comprises oxidizing the asphalt binder composition by bubbling or blowing an oxygen-containing gas (e.g., air) through the molten asphalt binder at an elevated temperature for a specific period of time (e.g., about 1 hour to about 72 hours). The length of time depends on various factors, such as the type of asphalt binder raw material used, the processing temperature, the air flow rate, the design of the process equipment, and the desired properties of the coating asphalt binder to be produced.

[0077] In some embodiments, the oxygen-enriched gas comprises about 25 wt % to about 35 wt % oxygen and about 65 wt % to about 75 wt % nitrogen. Chlorine-enriched air or pure oxygen may also be used in the air blowing step. A catalyst (e.g., ferric chloride, or any form of phosphoric acid, aluminum chloride, zinc chloride, and organic sulfonic acid) may be used in the oxidation process to achieve desired performance and to increase the reaction rate.

[0078] In some embodiments of a process for manufacturing a coating asphalt binder, a molten asphalt binder feedstock is loaded into a converter (oxidizer) at an elevated temperature, air is bubbled or blown through the molten asphalt binder and air blowing is performed until the asphalt binder reaches a target penetration value, for example, a penetration of 15 dmm but less than 20 dmm. The softening point, penetration and viscosity of the output asphalt binder material are mutually dependent on the selected input asphalt binder material, and one property may be adjusted independently without adjusting the other two properties to a corresponding degree. Depending on the nature of the asphalt binder, an air blowing process alone may not be sufficient to produce an asphalt binder that has properties that fall within each of the penetration, softening point and viscosity requirements to be considered a "coating" asphalt binder.

[0079] To achieve the desired asphalt properties for the roofing material, in some embodiments, the molten asphalt binder feedstock is "under-blown," whereby the asphalt binder is air-blown to a penetration value that falls within or slightly above the target penetration range for the coating asphalt binder (about 15-23 dmm), but has a softening point that is below the target softening point range, such as in the range of about 60° C. (140° F.) to about 85° C. (185° F.). "Under-blowing" means stopping the oxidation process before the penetration value is sufficiently reduced.

[0080] The process of underblowing the molten asphalt binder material can incorporate additives into the molten asphalt binder material to adjust the properties of the material to those required for a particular application. In some embodiments, wax pellets can be introduced into the molten asphalt binder to increase the softening point of the asphalt binder to a target softening point range while maintaining a desired penetration value. Other additives (e.g., polyphosphoric acid) can also be used to further soften the product. In some embodiments, sterols are the additives.

[0081] In some embodiments, rather than under-blowing the molten asphalt binder material, the molten asphalt binder is "over-blown" or air-blown to a penetration value that falls within or slightly below a target softening point range, such as a penetration value of about or slightly below 15 dmm. By over-blowing the molten asphalt binder, the resulting molten asphalt binder material may have a softening point that is above the target softening point range for the coating asphalt binder, such as between about 98.8°C and 116°C (210°F-240°F). Thus, in some embodiments, the over-blown molten asphalt binder material may have a first penetration value that falls within the target penetration range while having a first softening point that is above the target range.

[0082] Any suitable adhesive capable of being blown by air to achieve the properties of roofing asphalt can be used. In some embodiments, the asphalt adhesive is a petroleum-based adhesive. Suitable asphalt-based or asphalt adhesives include adhesives that meet ASTM D312, ASTM D3462, ASTM D2626, ASTM D-6373, ASTM D-946, AASHTO M320, AASHTO M332, AASHTO M226, AASHTO M20, ASTM D312, ASTM D3462 or ASTM D2626 and adhesives that meet ASTM 1-4 BURA models and also meet the specifications of coating asphalt adhesives.

[0083] In some embodiments, the adhesive is an aged adhesive. In some embodiments, the aged adhesive is obtained by extracting an asphalt adhesive from a roofing material. In some embodiments, the aged adhesive is an oxidized asphalt adhesive. In some embodiments, the oxidized asphalt adhesive is air blown for use in roofing materials. In some embodiments, the roofing materials include roofing tiles, roll roofing, and composite roofing. In some embodiments, asphalt is extracted from roofing tiles. There are two types of roofing tile waste. They are called broken roofing tiles and roofing tile scraps (also called instant roofing tile scraps). Broken roofing tiles are generated during the removal or replacement of existing roofs. Roofing tile scraps are generated when new asphalt shingles are trimmed to the required physical size during the production process. The quality of broken roofing tiles varies greatly.

[0084] In some embodiments, the asphalt binder contains other components in addition to sterols. These other components may include polymers, non-asphalt binders, adhesion promoters, softeners, revitalizers, and other suitable components.

[0085] Useful polymers include, for example, ethylene-vinyl acetate copolymers, polybutadiene, ethylene-propylene copolymers, ethylene-propylene-diene terpolymers, reactive ethylene terpolymers (e.g., ELVALOY TM), butadiene-styrene block copolymers, styrene-butadiene-styrene (SBS) block copolymers, isoprene-styrene block copolymers and styrene-isoprene-styrene (SIS) block copolymers, chloroprene polymers (e.g., neoprene), etc. Cured elastomeric additives may include ground tire rubber materials. For example, see California's 2015 Standard Specifications (Section 37, page 423) and Section 39 of Hot Mix Asphalt, starting at page 447, available from http: / / www.dot.ca.gov / distl / dllab / SECTION%2039%20%20HMA.pdf and http: / / caltrans-opac.ca.gov / publicat.htm.

[0086] In some embodiments, asphalt binder is extracted from recycled asphalt roofing materials (e.g., roofing tiles), which can then be used to produce new roofing materials. In some embodiments, sterols are added to aged asphalt binder that is regenerated or extracted from roofing materials (e.g., tiles). In other embodiments, sterols can be added to virgin, oxidized binder or newly manufactured roofing materials. Adding sterols to aged asphalt binder or virgin, oxidized asphalt binder or a combination thereof used to make roofing materials can extend the useful life of the roofing materials.

[0087] Added to roofing asphalt are a class of plant-derived chemicals called sterols. While phytosterols do not contain the same number of condensed rings or partially unsaturated rings as asphaltenes, they do have the advantage of not being linear or branched linear molecules. For example, sterols are able to modify or improve physical and rheological properties such as high temperature stiffness, effective temperature range, low temperature stiffness and relaxation properties of the asphalt binder.

[0088] In some embodiments, the sterol additive belongs to the triterpenoid class, particularly sterol or stanol. The disclosed sterol (e.g., triterpenoid) can work effectively with asphaltene. Asphaltene includes a wide range of condensed ring systems with a certain degree of unsaturation. In air-blown adhesives, the asphaltene content of a typical adhesive can be less than 10% to greater than 20% and to greater than 30%. According to ASTM D4124, asphaltene is generally described as a substance insoluble in n-heptane. The exact structure is unknown and is based on the performance behavior of different adhesives. The asphaltene structure in any two adhesives is unlikely to be the same, especially adhesives from different crude oil sources. Asphaltene gives the adhesive its color and rigidity, and its content increases as the adhesive ages. Generally, the higher the asphaltene content, the harder the adhesive, and the adhesive is less likely to relax. Therefore, adding RAP and / or RAS leads to an increase in asphaltene content. Increasing asphaltene content and other oxidation products (e.g., carbonyl compounds and sulfoxides) is the cause of the hardening of asphalt mixtures and their ultimate failure. Due to its unique chemical properties, asphaltene is not easily soluble in aliphatic chemicals. Aromatic solvents will readily dissolve asphaltenes, and aromatic process oils have been used in regeneration mixtures. However, these oils may contain polynuclear aromatic compounds (including listed potential carcinogens) and are therefore not ideal additives. Most vegetable based oils are straight or branched chain hydrocarbons with some degree of unsaturation and also contain carboxylic acid functional groups and are therefore not as effective in slowing the rate of aging as they are in softening the overall binder in the mixture.

[0089] Triterpenoids are the main categories of plant natural products, which include sterols, triterpenoid saponins and related structures. Triterpenoids can be natural or synthetic. Usually, triterpenoids are obtained by extracting from plant materials. The extraction process for separating triterpenoids is described in, for example, International Application Publication Nos. WO 2001 / 72315 A1 and WO2004 / 016336 A1, and its disclosure is incorporated herein by reference in its entirety.

[0090] Triterpenoids include phytosterols and phytostanols. The disclosed triterpenoids include any of the phytosterols mentioned herein in both esterified and non-esterified forms.

[0091] Exemplary phytosterols include: campesterol, stigmasterol, stigmasterol, β-sitosterol, Δ5-avenosterol, Δ7-stigmasterol, Δ7-avenosterol, brassicasterol, or a mixture thereof. In some embodiments, the sterol additive is a combination of different sterols. In some embodiments, the sterol additive is β-sitosterol as a pure sterol. In some embodiments, the sterol additive is a mixture of different pure sterols. In some embodiments, the pure sterol is: campesterol, stigmasterol, stigmasterol, β-sitosterol, Δ5-avenosterol, Δ7-stigmasterol, Δ7-avenosterol, brassicasterol, or a mixture thereof.

[0092] Commercially available pure sterols and mixtures of pure sterols include a sterol known as β-sitosterol (β-sitosterol: 40-60%; campesterol: 20-40%; stigmasterol: 5%) available from MP Biomedicals (Cat. No. 02102886). In some embodiments, the pure sterols may include pure cholesterol. In some embodiments, the pure sterols may have at least 70 wt.% sterols, and in some embodiments, may have at least 80 wt.%, at least 85 wt.%, or at least 95 wt.% sterols.

[0093] In some embodiments, the sterol additive is a crude sterol. Crude sterols can be obtained from plant sources, including modified or unmodified natural products containing different amounts of sterols, including a variety of plant sources, such as corn oil, wheat germ oil, sarsaparilla root, soybean pitch and corn oil pitch. For example, tall oil pitch can be obtained indirectly from the process of preparing paper from wood (especially pine). For example, tall oil is a by-product of wood pulping (e.g., by kraft paper process). When tall oil is distilled to produce tall oil fatty acids (TOFA) and tall oil rosin (TOR), the residue remaining in the distillation process is tall oil pitch. Tall oil pitch is an extremely complex substance that can contain rosin, fatty acids, oxidation products, wax compounds, high molecular weight alcohols, and esterified and non-esterified substances, a portion of which are sterols. In some embodiments, the source of crude sterols is a plant source. The plant sources of crude sterols are inexpensive because they are oil residues or tailings left by distillation or solvent extraction of wood-derived oils or vegetable oils or seed-derived oils.

[0094] In some embodiments, crude sterol is a mixture of different crude sterols. In some embodiments, crude sterol is a mixture, which includes: stigmasterol, β-sitosterol, campesterol, ergosterol, brassicasterol, cholesterol and lanosterol or a mixture thereof. In some embodiments, the crude sterol source includes: soybean oil, corn oil, rice bran oil, peanut oil, sunflower oil, safflower oil, cottonseed oil, rapeseed oil, coffee seed oil, wheat germ oil, tall oil and lanolin. In some embodiments, crude sterol includes a biologically derived source or a partial distillation residue of a biologically derived source. In some embodiments, the crude sterol source includes tall oil pitch, soybean oil or corn oil.

[0095] Any oil tailings or pitch from the disclosed plant sources are suitable sources of crude sterols. U.S. Patent 2,715,638, issued to Albrecht on August 16, 1955, discloses a process for recovering sterols from tall oil pitch wherein fatty acid impurities are removed by a neutralization process. The sterol esters are then saponified; the free sterols are then recovered and washed with isopropanol and dried.

[0096] In some embodiments, crude sterols are obtained from plant sources. Crude sterols may include components other than the desired sterol or sterols. Exemplary plant sources of crude sterols include: tall oil pitch, crude tall oil, sugarcane oil, hot well scum, cottonseed pitch, soybean pitch, corn oil pitch, wheat germ oil or rye germ oil. In some embodiments, tall oil pitch is the source of crude sterols. Tall oil pitch may contain about 30% to 40% unsaponifiable molecules. Unsaponifiables are molecules that do not react with alkaline hydroxides. The fat and rosin acids remaining in tall oil pitch are easily reacted (saponified) with potassium hydroxide or sodium hydroxide, so the unsaponifiables can be easily separated. It has been shown that up to 45% of the unsaponifiable fraction may include sitosterol. Therefore, a tall oil pitch sample may contain about 13.5wt.% to 18wt.% of sterol molecules. In some embodiments, crude sterols may have a purity less than food grade (eg, less than 85 wt. % sterols) or contain more than 85 wt. % sterols, but may also contain impurities or contaminants that render the material unsuitable for use in food.

[0097] In some embodiments, the crude sterol can be of animal origin. In some embodiments, the sterol of animal origin is cholesterol.

[0098] It should be understood that the disclosed sterols can be used in any combination including animal-derived, plant-derived, pure, crude or recycled sterols. For example, in some embodiments, the sterols are pure sterols from plants. In some embodiments, the sterols are pure sterols from a combination of plant and animal sources. In some embodiments, the sterols are crude sterols from a combination of plant and animal sources. In some embodiments, the recycled sterols are sterols from aged asphalt binders containing sterols.

[0099] In some embodiments, the sterol added to the asphalt binder is a recycled sterol or a neosterol in the range of about 0.5 wt.% to about 15 wt.%, about 1 wt.% to about 10 wt.%, or about 1 wt.% to about 3 wt.% of the asphalt binder. The sterol added to the asphalt may, for example, be about 0.5 wt.% to about 15 wt.%, about 1 wt.% to about 10 wt.%, or about 1 wt.% to about 3 wt.% of the asphalt binder. In some embodiments, the sterol added to the asphalt binder may, for example, be about 0.5 wt.% to about 15 wt.%, about 1 wt.% to about 10 wt.%, or about 1 wt.% to about 3 wt.% of the original oxidized asphalt binder.

[0100] In some embodiments, the sterol is a combination of a recycled sterol and a neosterol. In some embodiments, such recycled sterol and neosterol include a ratio of 5:95 to 95:5 recycled sterol:neosterol. In some embodiments, the sterol combination includes a ratio of at least 20:80, 30:70, or 40:60 recycled sterol:neosterol, and in some embodiments, includes a ratio of less than 80:20, 70:30, or 60:40 recycled sterol:neosterol.

[0101] In some embodiments, the neosterol is a pure sterol, a crude sterol, or a combination thereof. In some embodiments, the sterol is a sterol combination, wherein the pure sterol:crude sterol is added to the asphalt binder in a range of about 0.5 wt.% to about 15 wt.%, or about 1 wt.% to about 10 wt.%, about 1 wt.% to about 3 wt.% of the original oxidized binder in the asphalt composition. In some embodiments, the sterol combination includes a pure sterol:crude sterol ratio of 5:95 to 95:5. In some embodiments, the sterol combination includes a pure sterol:crude sterol ratio of at least 20:80, 30:70, or 40:60, and in some embodiments, includes a pure sterol:crude sterol ratio of less than 80:20, 70:30, or 60:40.

[0102] In some embodiments, sterols may modify, slow down, or retard degradation of rheological properties due to aging of a binder containing recycled asphalt materials (eg, RAS and / or RAP) or an oxidized binder.

[0103] The sterols may be added to an asphalt binder that is aged or virgin oxidized and used to produce a roofing material by impregnating or coating the roofing material or a combination thereof. In some embodiments, the sterols may be added to the virgin or aged asphalt binder prior to oxidation or air blowing, or provided by recovering the sterols from an aged asphalt binder containing the sterols prior to aging. In other embodiments, the sterols may be added to the virgin or aged asphalt binder after oxidation or air blowing, or provided by recovering the sterols from an aged asphalt binder containing the sterols prior to aging.

[0104] In some embodiments, at least a portion of the top surface of the roofing material is coated with a composition comprising a coating asphalt binder and a sterol.

[0105] The present application also shows that sterols can be present in aged asphalt and not be consumed or react with the aged asphalt. This provides an additional source of sterols so that recycled sterols (present in aged asphalt) can be used with virgin material or even aged asphalt in RAP form, and the aging delay benefits of recycled sterols can be used to help slow the aging or aging rate of new blends. For example, the present application shows that based on the data generated, the PAV aging of a RAP blend containing 10% sterols and subjected to 10 to 12 years of field aging can be approximately 60 hours.

[0106] Thus, if a 50% binder replacement using RAP containing recycled sterols is used with the original binder, the final blend may contain 5% sterols. The aging rate of this new blend is based on the 5% newly added sterols. An additional 5% of neosterols can be added to the original binder to bring the final level back to 10%. In other words, if desired, the aged asphalt can be added with additional neosterols to reach an amount or level suitable for providing anti-aging properties.

[0107] Thus, the present application provides an additional source of sterols that may have been used in asphalt pavement or asphalt shingles, i.e., an aged asphalt binder in which the binder already contains sterols. In other words, the sterols that may be used are those present in existing asphalt pavements or asphalt shingles. These "recycled sterols" have been found to provide anti-aging properties similar to new sterols (i.e., sterols that have not been used in asphalt pavement or oxidized asphalt applications). The recycled sterols are provided in the form of an asphalt binder composition comprising the sterols.

[0108] Such compositions and methods save raw materials, achieve economic and environmental protection, while observing the attendant benefits of adding new sterols. The resulting benefits include improved physical and rheological properties, such as stiffness, effective temperature range and low temperature performance.

[0109] In some embodiments, the sterol is obtained from recycled sterol. In some embodiments, the recycled sterol is a sterol-containing asphalt binder. It should be understood that different types of sterols can be added to the asphalt composition to provide an appropriate amount of sterols to provide the anti-aging properties of the sterols. In other words, 10wt% sterols present in an aged asphalt binder containing recycled sterols can be used as sterols in the asphalt composition to provide anti-aging properties. On the other hand, the same 10wt% sterols present in an aged asphalt binder containing recycled sterols can be used as sterols together with new sterols to provide an amount suitable for providing anti-aging properties to the asphalt composition.

[0110] Different parameters are used to measure how effectively different binders react to aging, or how effectively different additives (such as sterols) affect the response of binders to aging. ΔTc is calculated by subtracting the m critical temperature from the S critical temperature. Anderson et al. (Anderson, RM, King, GN., Hanson, DI, Blankenship, PB "Evaluation of the Relationship between Asphalt Binder Properties and Non-Load Related Cracking," Association of Asphalt Paving Technologists, Volume 80, pp 615-663 (2011)) showed that larger ΔTc values ​​are associated with fatigue cracking of asphalt pavements. Specifically, the study showed that cracking may occur when ΔTc is 5°C or higher. Anderson et al. used a procedure that subtracted the S critical temperature from the m critical temperature, so the more positive the value of ΔTc, the greater the likelihood of fatigue cracking. The asphalt research community has reversed the above calculation, and now the more negative the ΔTc is, the more difficult it is for the binder to have relaxation stress, and therefore the more brittle it will be, indicating that the binder performance has declined.

[0111] In this application, determination of the m-critical rating of oxidized binders is used as a means of identifying aging improvements in oxidized binders with added sterols. Changes in m-critical can also quantify the rate or degree to which the embrittlement level of the oxidized asphalt increases. There is currently no m-critical requirement for oxidized binders.

[0112] In this application, determination of the S-critical rating of oxidized adhesives is used as a means to identify changes in low temperature stiffness properties of oxidized adhesives with added sterols when subjected to aging. Currently there is no S-critical requirement for oxidized adhesives.

[0113] To determine the ΔTc parameter, the 4 mm DSR test procedure and data analysis method from Western Research Institute as described above was used. The DSR test procedure and method are also disclosed in International Applications PCT / US16 / 37077 filed on June 10, 2016, PCT / US2016 / 064950 filed on December 5, 2016, and PCT / US2016 / 064961 filed on December 5, 2016, each of which is incorporated herein by reference in its entirety.

[0114] The ΔTc parameter can be measured using a 4 mm DSR test as described in Sui, C., Farrar, M., Tuminello, W., Turner, T., A New Technique for Measuring low-temperature Properties of Asphalt Binders with Small Amounts of Material, Transportation Research Record No 1681, Transportation Research Board, Washington, DC, US, Vo1. 2179, 1 December 2010, pages 23-28. See also Sui, C., Farrar, MJ, Harnsberger, P M., Tuminello, WH, Turner, TF, New Low Temperature Performance Grading Method Using 4mm ParallelPlates on a Dynamic Shear Rheometer TRB Preprint CD, 2011; and by Farrar, M., et al., (2012), Thin Film Oxidative Aging and Low Temperature Performance Grading Using Small Plate Dynamic Shear Rheometry: An Alternative to Standard RTFO, PAV and BBr.Eurasphalt&Eurobitume 5th E&E Congress-2012Istanbul(pp.Paper O5ee-467).Istanbul: Foundation Eurasphalt.

[0115] The ΔTc parameter can also be measured using a bending beam rheometer (BBR) test procedure based on AASHTO T313 or ASTM D6648. It is important that when using the BBR test procedure, the test is performed at a sufficient number of temperatures so that for a stiffness failure criterion of 300 MPa and a creep or m-value failure criterion of 0.300, the following results are obtained: one result is below the failure criterion and one result is above the failure criterion. In some cases, for adhesives with ΔTc values ​​less than -5°C, this may require BBR testing at three or more test temperatures. When the above BBR standard requirements are not met, the ΔTc value calculated from the data may not be accurate.

[0116] Although the ΔTc value of oxidized asphalt has not been determined, the present application has determined the ΔTc of oxidized asphalt to which sterols have been added and then aged, and uses the ΔTc value to quantify the rate of embrittlement change of the oxidized asphalt. The ΔTc values ​​of oxidized asphalt measured in the present application are all negative, and the more negative the ΔTc value, the more brittle the binder.

[0117] Another indicator of the ability of the sterol to retard or slow the development of brittleness in an adhesive is the rheological index or R-value of the adhesive. The R-value data are shown in Table 1 and plotted on Figure 3 The rheological index is defined as: the glass modulus (G * The logarithm of the modulus of stiffness of the adhesive (G * ). The adhesive crossover frequency is the point at which the storage modulus (G′) and loss modulus (G″) of the adhesive are equal, at which point the phase angle of the adhesive is 45°. These values ​​are readily obtained by dynamic shear rheology testing over a range of temperatures and frequencies. As the adhesive ages, its R-value increases because, while the glass modulus remains relatively constant over the range of 1.0 to 1.5 GPa, the crossover frequency temperature increases (gets warmer), so the modulus at the crossover frequency decreases due to the warmer temperature. The net effect is that the difference between the two moduli becomes larger. For all samples, the R-value data reported in Tables 1 and 2 uses a static glass modulus of 1E9 Pascals.

[0118] In some embodiments, the roofing material comprises an oxidized asphalt binder containing sterols, the oxidized asphalt binder containing sterols being capable of providing a Tm critical temperature that is 2°C to 5°C lower than the Tm critical temperature of an untreated roofing adhesive without sterols and a ΔTc that is 2°C to 5°C higher than an oxidized binder without added sterols. In some embodiments, the roofing material comprises an asphalt binder containing sterols, the asphalt binder containing sterols being capable of providing a ΔTc improvement of greater than or equal to 5.0°C after aging at 100°C PAV for 0, 10, 20, 40 hours compared to a similarly aged, oxidized binder without sterols. In further embodiments, the roofing material comprises a coating asphalt binder containing sterols, the coating asphalt binder containing sterols having a less negative ΔTc value and a lower R value with aging when compared to a similarly aged roofing material without sterols.

[0119] In some embodiments, the roofing material is a filled product in which a mineral filler is added to an oxidized adhesive. The sterol may be added to the oxidized adhesive before or after the filler is added. The filler content may range from 1 wt % to 80 wt % of the final roofing product. The sterol may be added as a weight percentage of the filled roofing material, or may be added as a weight percentage to the oxidized adhesive before the filler is added.

[0120] Other physical and chemical composition properties that indicate binder aging are rheological indices, known as R-values; As the binder ages, the asphaltene content in the binder increases. Asphaltene is defined as the portion of bitumen that is insoluble in n-heptane. Asphaltene has a certain molecular weight (1000 Daltons or more), consists of fused ring structures and is aromatic. As the binder ages, asphaltenes increase, while cyclic compounds (polar aromatic compounds) decrease, resins increase, and saturation tends to change very little. The colloid index (CI) reflects the overall change in the chemical composition of the asphalt due to aging. The CI is calculated as follows:

[0121] The R-value of an adhesive increases as the adhesive ages. This is because the R-value is calculated as the complex shear modulus (G * ) and the complex shear modulus (G * ) (usually set equal to 1E9 Pascals). As the adhesive ages, G * As the adhesive becomes more brittle, G * must be reduced to achieve a phase angle of 45°. Because the logarithm of the glass modulus does not change or changes only slightly, the difference between the logarithm of the glass modulus and the logarithm of the modulus at a phase angle of 45° becomes larger, resulting in an increase in the R value as the adhesive ages.

[0122] The R-value is determined from the rheological properties of the binder and the asphaltene content is obtained by chemically separating the major constituent fractions that comprise the bituminous binder. Both properties are affected by binder aging, but since their properties are not determined from the same type of test, the results for asphaltene content and R-value are determined independently; the results of one test do not affect the other. This is important when showing the benefits of sterols in retarding binder aging. For example, see the following references related to the development of R values: SHRP-A-369 "Binder Characterization and Evaluation, Volume 3: Physical Characterization" pp: 25-26 Published by Strategic Highway Research Program, National Research Council, Washing, DC 1994 National Academy of Sciences 2101 Constitution Ave, NW> Washington, DC 20418; "Interpretation of Dynamic Mechanical Test Data for Paving Grade AsphaltCements" Donald W.Christensen, Jr. and David A.Anderson Proceedings of the Association of Asphalt Paving Technologists, Vol 61, 1991, pp: 77-80 "PhysicalProperties of Asphalt Cement and the Development of Performance-RelatedSpecifications" David A.Anderson, Donald W.Christensen, and Hussain BahiaAssociation of Asphalt Paving Technologists, Vol.60, 1990, pp437-475. Example

[0123] The disclosed compositions are further illustrated in the following non-limiting examples. Various modifications and variations to the disclosed compositions will be apparent to those skilled in the art without departing from the scope of the invention. Example 1

[0124] The following study demonstrates that the presence of sterols in asphalt binder recovered from new manufacturer's shingle waste (typically, three shavings cut from cutting and laminating and waste) delays or slows the rate of aging of the recovered asphalt binder relative to untreated asphalt binder from new manufacturer's shingle waste.

[0125] Untreated asphalt binder and two sterol-treated binder samples were tested in original conditions (i.e., unaged) and after 20, 40, and 60 hours of PAV aging according to ASTM D 6521. PAV aging is commonly used to evaluate the aging performance of asphalt paving binders and for these samples, PAV aging was used as a quick means of evaluating the ability of the sterols to retard or slow the aging rate of the oxidized binder.

[0126] The sterols used were a mixed sterol called β-sitosterol (β-sitosterol: 40-60%; campesterol: 20-40%; stigmasterol: 5%) obtained from MP Biomedicals (Cat. No. 02102886).

[0127] The low temperature data, ΔTc, and R-value data provided in Table 1 were obtained using the 4 mm dynamic shear rheometer (DSR) test method proposed by Sui et al. (2010), Sui et al. (2011), and Farrar et al. (2012). The high temperature results were obtained using the 25 mm DSR test method according to ASTM D7175. Table 1. Rheological properties of adhesives plus sterols recovered from tile waste Sample description Aging, PAV hours Sterol% Ts critical, ℃ Tm critical, ℃ ATc,℃ R-Value 1kPa stiffness temperature, ℃ Adhesives recycled from manufacturers’ waste 0 0 -31.15 -22.15 -9.00 3.167 138.7 Adhesives recycled from manufacturers’ waste 20 0 -27.64 -3.75 -2389 3.656 154.8 Adhesives recycled from manufacturers’ waste 40 0 -26.56 -0.23 -26.33 3.762 179.2 Adhesives recycled from manufacturers’ waste 60 0 No data No data No data No data No data 10-01-13-E+5% sterol 0 5 -30.43 -27.01 -342 2.677 119.5 10-01-13-E+5% sterol 20 5 -26.84 -18.15 -8.69 3.038 139.7 10-01-13-E+5% sterol 40 5 -26.42 -1398 -12.44 3.257 150.1 10-01-13-E+5% sterol 60 5 -24.85 -5.72 -19.14 3.471 161.5 10-01-13-E+75% sterol 0 75 -29.80 -28.89 -0.91 2.476 112.4 10-01-13-E+75% sterol 20 75 -27.53 -22.38 -515 2.820 130.2 10-01-13-E+75% sterol 40 75 -2530 -16.90 -8.40 3.030 141.4 10-01-13-E+75% sterol 60 75 -2348 -9.58 -139 3.223 1476

[0128] As shown in Table 1, no data were generated for the 60-hour PAV aging condition for the original (i.e., unaged, untreated) recycled adhesive. The 60-hour aged samples, although produced, were brittle and could not be liquefied to the extent that they could be tested without excessive heating, which would change the properties of the adhesive. However, the data in Table 1 as a whole show the benefit of adding sterols to the adhesive recycled from the manufacturer's waste prior to aging.

[0129] The results of Table 1 are also plotted graphically and shown in Figure 1-3 middle. Figure 1 Shown is the temperature at which the stiffness of the adhesive is 1 kPa, measured by dynamic shear rheometer according to ASTM D7175, using a 25 mm diameter plate-plate geometry at a 1 mm gap.

[0130] Figure 1 The data in show that the addition of 5% and 7.5% sterols reduces the temperature at which the pristine adhesive (unaged) sample reaches a stiffness of 1 kPa.

[0131] The 1 kPa stiffness temperature of the 5% sterol sample without additional aging decreased by 19.2 °C, while that of the 7.5% sterol sample decreased by 26.3 °C. Figure 1 The data also showed that the 5% sterol sample required 20 hours of PAV aging to reach the 1 kPa stiffness temperature of the original unaged adhesive at zero aging time, while the 7.5% sterol sample required 40 hours of PAV aging to reach the 1 kPa stiffness temperature of the original adhesive at zero aging time.

[0132] Figure 2 is a graph of the Tm critical of the adhesive at each aging condition. Ts critical and Tm critical are defined as the temperatures at which the bending beam stiffness value = 300 MPa and the bending beam relaxation temperature = 0.300. The test method and the method for determining these results are described in ASTM 6648. Figure 2 It is shown that the Tm critical temperature of the recycled tile waste (without sterols) increases at a faster rate than the samples containing 5% and 7.5% sterols. As mentioned previously, the low temperature data were obtained using the 4 mm DSR geometry program developed by Western Research Institute.

[0133] The brittleness of the recycled, untreated tile waste adhesive resulted in a test result with a Tm threshold that was higher (warmer) than the Tm threshold for any of the sterol treated samples. The warmer low temperature failure values ​​indicate that the brittleness of the adhesive is increasing and the likelihood of low temperature failure will increase. Although the sterol treated samples aged based on the increase in their Tm thresholds, the brittleness was different from the original, unaged adhesive. The ΔTc temperature values ​​shown in Table 1 demonstrate the reduction in brittleness. Although the Ts threshold temperatures of the sterol treated samples were similar to the Ts threshold temperatures of the untreated recycled tile waste adhesive at 40 hours of PAV aging, the ΔTc values ​​for the sterol samples were significantly better (less negative) because the sterols retard or slow the increase in the adhesive's creep relaxation temperature or Tm threshold. It is important to recognize that adhesive relaxation (not adhesive stiffness at low temperatures) is a measure of adhesive brittleness. The data in Table 1 show that none of the sterol treated samples after 60 hours of PAV aging reached the same ΔTc values ​​as the original adhesive at 20 hours of PAV aging.

[0134] Table 1 shows that the R-values ​​for all tested blends increased steadily. Similar to the ΔTc values, the R-values ​​for the sterol samples after 60 hours of PAV aging never reached the levels achieved by the original untreated adhesive at 20 hours of PAV aging. These results are Figure 3, where the 60-hour R-value data for the 7.5% sterol sample is similar to the original adhesive at zero aging time. These data further explain why the brittleness present in the original adhesive sample is not prevalent in the sterol sample. Example 2

[0135] Sterols were also evaluated using oxidized coating asphalt binders. In the following data, coating asphalt binders were treated with three loading levels of sterols followed by PAV aging at 10, 20 and 40 hours and then the changes in the high and low temperature properties of the aged samples were determined as described in Example 1.

[0136] A coating asphalt binder obtained from Malarky Roofing was used. Sterol concentrations of 3%, 5%, and 8% were mixed into the coating asphalt binder according to ASTM D 6521 and PAV aged at 100°C for 10, 20, and 40 hours. The test results of these samples are shown in Table 2. Table 2. Rheological properties of coating asphalt binder blends with sterols Sample description aging Sterol% Ts critical Tm critical ΔTc R-Value Temperature at 1 kPa stiffness Tile Coating Asphalt Binder 0 0 -33.14 -11.03 -22.11 3.785 126.4 Tile Coating Asphalt Binder 10 0 -32.35 -4.10 -28.25 3.956 143.2 Tile Coating Asphalt Binder 20 0 -31.01 -1.33 -29.68 4.090 153.5 Tile Coating Asphalt Binder 40 0 -29.90 4.75 -34.65 4.195 175.4 Tile coating + 3% sterol 0 3 -34.23 -18.23 -16.00 3.362 115.6 Tile coating + 3% sterol 10 3 -31.55 -10.41 -21.14 3.764 132.3 Tile coating + 3% sterol 20 3 -32.42 -7.89 -24.54 3.855 142.5 Tile coating + 3% sterol 40 3 -28.32 2.32 -30.64 4.050 157.3 Tile coating 5% sterol 0 5 -34.76 -22.00 -12.76 3.359 110.4 Tile coating 5% sterol 10 5 -32.56 -15.96 -16.60 3.501 125.5 Tile coating 5% sterol 20 5 -30.71 -10.45 -20.27 3.621 137.8 Tile coating 5% sterol 40 5 -27.77 -0.07 -27.70 3.854 151.2 Tile coating 8% sterol 0 8 -34.07 -27.02 -7.06 2.949 104.1 Tile coating 8% sterol 10 8 -31.52 -20.71 -10.81 3.225 118.1 Tile coating 8% sterol 20 8 -30.88 -15.28 -15.60 3.265 122.6 Tile coating 8% sterol 40 8 -27.25 -7.25 -19.99 3.505 137.1

[0137] A review of the temperatures at which the binders achieved 1 kPa stiffness showed that the 3% sterol sample had a 4°C higher stiffness temperature after 40 hours of PAV aging compared to the untreated coating asphalt binder at 20 hours of PAV aging. The 5% sterol sample had a 2°C lower temperature at 40 hours of PAV aging compared to the untreated coating asphalt binder at 20 hours of PAV aging. The 8% sterol sample had a 1 kPa stiffness temperature of 137.1°C after 40 hours of PAV aging compared to 126°C for the unaged, untreated sample. For the 10 hour PAV aged sample, the untreated sample had a 1 kPa stiffness temperature of 143°C, meaning that the 8% sterol sample had a 1 kPa stiffness temperature of 6°C lower after 40 hours of PAV aging than the untreated sample after 10 hours of PAV aging.

[0138] The high temperature data in Table 2 are plotted on Figure 4 middle. Figure 4 The sterol dosage response is shown. Each successively higher sterol dosage level reduces the rate at which the high temperature value increases for the treated sample compared to the untreated sample.

[0139] Figure 4A graph showing high temperature paint asphalt binder samples at different aging times. The regression plot shows that the addition of sterols delays or slows the rate at which the high temperature performance of the paint asphalt binder increases with aging in a dosage-dependent manner. For the unaged samples, the differences for 3% sterol, 5% sterol, and 8% sterol were 10.8°C, 16°C, and 22.3°C, respectively, but after aging for 40 hours, the differences for the 3% sterol and 5% sterol samples increased by 8°C, and the 8% sterol blend increased by 16°C.

[0140] Evaluation of the Tm threshold data for the coating asphalt binder samples in Table 2 shows that the sterols reduced the Tm threshold temperature of the unaged samples by 7°C for 3% sterol, 11°C for 5% sterol, and 16°C for 8% sterol. However, the data also show that the Tm threshold values ​​of the sterol samples increased at a faster rate than the Tm threshold value of the untreated binder, such that at 40 hours of aging, the Tm threshold value of the 3% sterol blend was 2.4°C lower than the untreated coating asphalt binder, the Tm threshold value of the 5% sterol blend was 4.7°C lower than the untreated coating asphalt binder, and the Tm threshold value of the 8% sterol blend was 12°C lower than the untreated coating. Sterol concentration showed a dosage-dependent response to Tm threshold. Figure 5 The data plot in shows that the Tm critical aging rate decreases with increasing sterol levels. Based on the slope of the data plot, Tm critical increases at a faster rate than the untreated binder for all sterol treatment levels, although the Tm critical aging rate is clearly improved with the dosage response. The coating asphalt is the most oxidized air-blown asphalt. The more oxidized the binder, the more sterol is required to retard the Tm critical aging rate. Figure 4 This is clearly illustrated by the data shown graphically in Figure 3. The 3% and 5% sterol loadings had almost identical Tm critical aging slopes, but the Tm critical aging slope for 8% sterols was reduced compared to the 3% and 5% samples.

[0141] The reason for this reaction of the paint asphalt binder samples compared to the binder recovered from manufacturer waste lies in the component makeup of the binder. Tables 3 and 4 show the IATROSCAN results for the samples shown in Tables 1 and 2, respectively. One variation on these data is that the saturate content of the binder recovered from shingle waste was 3% to 5.5% lower than the saturate content of the paint asphalt binder. This higher saturate content is likely due to the addition of softening oil prior to blowing the asphalt to create the paint, as typical saturate levels for most asphalts are in the 6%-8% range. Regardless of the source, the saturate levels were higher in the paint asphalt binder. Additionally, for the same aging time and sterol content, the paint asphalt binder had a higher asphaltene content than the recycled shingle waste binder ( Figure 6). Both of these factors adversely affect the relaxation of the adhesive with aging, as quantified by the Tm critical. Without being bound by any theory, sterols can affect adhesive performance by dispersing or disrupting asphaltenes that develop with aging. Higher levels of asphaltenes require higher levels of sterols to reverse the effects of asphaltenes growth due to high levels of oxidation.

[0142] Check Figure 5 From a plot of the critical Tm versus PAV aging hours, the regression equation can be used to calculate the number of PAV aging hours required before the sterol regression data intersects with the untreated sample. For a 3% sterol loading, the time would be a total of 65 PAV hours, for 5% sterols the time would be 84 PAV hours, and for 8% sterols the time would be 214 PAV hours. These results provide a means of determining a reasonable amount of sterol to effectively protect the coating asphalt binder from degradation to the same conditions as the untreated coating asphalt binder. A 3% loading would only require a total of 65 PAV hours. Figure 5 The aging time required for the 5% loading would be twice that shown and would probably be considered a cost effective loading depending on the life of the tile predicted by the 40 hour PAV aging. Figure 5 The 5 times aging time of 40 hours shown provides theoretical protection. The 8% loading level is probably higher than required for all but the most extreme cases.

[0143] Considering the changes of Ts critical and Tm critical, ΔTc data ( Figure 7 ) show that the 40 hour aged 3% sterol ΔTc values ​​are similar to the 20 hour aged untreated sample, and the 40 hour aged 5% sterol ΔTc is slightly better than the 10 hour aged untreated sample. The 40 hour PAV of 8% is about 3°C ​​better than the ΔTc of the original paint asphalt binder without additives. These data show that these sterol loadings are able to modify the brittleness of the paint asphalt binder over extended aging times.

[0144] Using the same regression equation for the ΔTc data, the 5% sterol blend would require 132 PAV hours of aging to achieve the same ΔTc as the untreated coating asphalt binder, while the 8% sterol blend would require 475 PAV hours of aging to be consistent with the untreated coating asphalt binder. These values ​​are approximately twice the values ​​determined for the Tm critical results. This is because when calculating ΔTc, both Ts critical and Tm critical data are used in the calculation. Both Ts critical and Tm critical degrade as the binder ages, but it is clear from Table 2 that Ts critical degrades slower than Tm critical and ΔTc decreases slower than Tm critical. Table 3. Composition and properties of adhesives recovered from tile waste Table 4. Composition and properties of asphalt binder for coatings Sources of Roofing Asphalt aging Asphaltene Resin Cyclic compounds Saturates Cl Paint bitumen, clean original 30.9 17.9 40.0 11.1 1.379 Paint bitumen, clean 10 hours PAV 33.8 20.2 34.3 11.7 1.198 Paint bitumen, clean 20 hours PAV 33.7 20.9 33.4 12.0 1.188 Paint bitumen, clean 40 hours PAV 37.7 22.3 27.4 12.6 0.988 Paint asphalt + 3% sterol original 30.6 22.5 35.9 11.0 1.404 Paint asphalt + 3% sterol 10 hours PAV 32.6 25.6 31.1 10.7 1.309 Paint asphalt + 3% sterol 20 hours PAV 33.5 24.3 30.3 11.9 1.203 Paint asphalt + 3% sterol 40 hours PAV 36.0 26.1 26.0 11.8 1.090 Paint asphalt + 5% sterol original 29.9 21.6 38.6 9.9 1.513 Paint asphalt + 5% sterol 10 hours PAV 31.2 24.3 34.1 10.4 1.404 Paint asphalt + 5% sterol 20 hours PAV 33.4 26.8 27.8 11.9 1.205 Paint asphalt + 5% sterol 40 hours PAV 35.3 29.3 24.3 11.2 1.153 Paint asphalt + 8% sterol original 28.5 24.7 37.4 9.4 1.639 Paint asphalt + 8% sterol 10 hours PAV 32.6 26.8 29.6 11 1.294 Paint asphalt + 8% sterol 20 hours PAV 33.8 31.4 24.6 10.1 1.276 Paint asphalt + 8% sterol 40 hours PAV 34.3 30.4 24.2 11.1 1.203

[0145] An evaluation of the changes in R values ​​based on sterol content and aging time was also performed, and the data are plotted in Figure 8 middle. Figure 8 Both Table 2 and Table 3 show that the R-values ​​for the unaged 3% sterol are nearly identical to those for the 5% sterol sample, which is inconsistent with the rest of the data. Repeated testing confirmed this result. One possible explanation is that the 3% sterol initially had a large effect on the properties of the coating asphalt binder, but as aging progressed, this effect was no longer sustained due to the low sterol loading. Figure 8 and Fig. 9 It was shown that the results for the 5% and 8% sterols varied less with aging than the 3% sterol samples. Fig. 9 The data plotted in includes only data from PAVs aged 10, 20, and 40 hours to eliminate data inconsistencies for the unaged blends. The R-values ​​for the 3% sterols aged 40 hours are slightly greater than the untreated sample aged 10 hours. The R-values ​​for the 5% sterols aged 40 hours are lower than the untreated sample at 10 hours and similar to the 3% sterols blend at 10 hours. Figure 7 The ΔTc data in also provide the same conclusion. Fig. 9 The data regression in also showed that the R-values ​​of the coating asphalt binder plus sterol samples increased at a similar or slightly lower rate than the untreated samples. However, the initial decrease in R-values ​​was dosage dependent, and the R-values ​​followed an aging path based on the starting point of the initial blend, especially for the 5% and 8% blends. The decrease in R-values ​​and the improvement in ΔTc due to the addition of sterols indicate that the sterols are able to reduce the low temperature brittleness of the coating asphalt binder as the binder samples age. Example 3

[0146] Example 3 provides aging data for untreated filled coating binder and 5% and 8% sterol samples. Filled coating binder is a mineral filler in the coating. Prior to testing, the samples were aged in the PAV for 10, 20 and 40 hours. An estimate of the amount of filler in the coating was determined by dissolving the filled coating in toluene and washing the sample until it became transparent through the filter. Asphalt quality was determined by the n-heptane insolubility test procedure according to ASTM D3279. The filler amount was determined to be 41 wt % of the total asphalt binder. Sterols were added based on the weight percentage of the total asphalt binder. The data for these samples are shown in Table 5. Table 5. Rheological properties of asphalt binders of filler coatings containing sterols Sample description aging % Sterols Ts critical Tm critical ΔTc R-Value 1 kPa Stiffness Temperature Filled tile coating asphalt 0 0 -15.93 -5.76 -10.17 2.538 144.6 Filled tile coating asphalt 10 0 -11.69 2.10 -13.79 2.624 154 Filled tile coating asphalt 20 0 -10.06 7.82 -17.88 2.789 161.7 Filled tile coating asphalt 40 0 -11.28 9.95 -21.23 2.956 169.7 Filled tile coating + 5% sterol 0 5 -19.52 -25.24 5.72 1.807 106.5 Filled tile coating + 5% sterol 10 5 -17.36 -21.61 4.25 1.949 120.8 Filled tile coating + 5% sterol 20 5 -14.81 -17.76 2.95 2.092 127.4 Filled tile coating + 5% sterol 40 5 -12.75 -15.05 2.30 2.102 138.2 Filled tile coating + 8% sterol 0 8 -20.15 -25.32 5.16 1.658 93.6 Filled tile coating + 8% sterol 10 8 -17.70 -23.01 5.32 1.864 103.4 Filled tile coating + 8% sterol 20 8 -16.20 -22.24 6.04 1.744 111.7 Filled tile coating + 8% sterol 40 8 -14.05 -19.98 5.93 1.909 118.4

[0147] The temperature at which the filled coating asphalt binder was equal to 1 kPa was lower than that of the unfilled coating asphalt binder without sterols (Example 2) and significantly lower than that of the unfilled coating asphalt binder containing 5% and 8% sterols. This may be due to the sterol loadings of 8.4% and 13.5% sterol based on the binder-only content of the filled coatings, and the mass percentage of binder in the filled coatings was 59% based on our analysis. The Tm critical temperature results for the filled coatings are increasingly colder (implying that the specification criteria for low temperature relaxation occur at colder temperatures). However, for the untreated 5% and 8% sterol loadings, the Ts critical temperature is warmer than that of the unfilled samples. In the case of the Tm critical, the test results can be attributed to the higher sterol concentration as a percentage of the binder; alternatively, the sterols do not appear to have any beneficial effect on the Ts critical, and the higher binder stiffness of the filled coating asphalt may simply be a function of the hardening effect of the filler. The R values ​​of the three samples changed slightly as each individual sample aged, but the R values ​​showed a decreasing trend from the untreated sample to the 5% and 8% sterol samples, as shown in Table 5. Fig.10 is a comparison of the Tm cutoffs of unfilled and filled coating binder samples as a function of PAV aging time. Shown are data for untreated samples of each coating material as well as 5% and 8% blends. The effect of the filler appears to be to even out the aging of the sterol-containing filled binder blends. The unfilled and filled untreated samples have similar Tm cutoffs at zero aging time, but the trend lines diverge to the point where the Tm cutoff of the filled binder is 8.6°C cooler than the unfilled binder after 40 hours of PAV aging. For the 5% sterol sample, the Tm cutoff of the filled sample is 15°C cooler, and for the 8% blend, the Tm cutoff of the filled sample is 12.75°C cooler. In addition, the slope for the 8% sterol-filled binder is lower than any other sample, meaning that this sample is not greatly affected by additional aging. It is again worth pointing out that based on the sterol concentration as a percentage of the binder, the filled asphalt sterol concentration is higher because of the presence of the filler and the sterol concentration is based on the filler mass rather than just the binder mass.

[0148] Fig.11 is a comparison of the 1 kPa stiffness temperature for filled and unfilled coating binders in the untreated condition and at 5% and 8% sterol loadings. The data indicate that the addition of sterols to the filled coatings reduced the high temperature aging rate of the filled coatings for each of the comparative samples, but this is likely due to the difference in sterol to binder loading between the unfilled and filled samples. Regardless of the loading difference, Fig.11 The data plotted in show that it is possible to reduce the 1 kPa stiffness temperature of a filled adhesive compared to an unfilled adhesive, and that it is also possible to reduce the high temperature aging rate of a filled system relative to an unfilled system. Example 4

[0149] For these experiments, PG 58-28 asphalt binder was aged in thin film form at 135°C for an average of 70-72 hours to simulate an aged asphalt binder. Different amounts of sterols were added to the aged asphalt binder. Sterols were purchased from MP Biomedicals (Solon, OH, catalog number 02102886) (β-sitosterol: 40%-60%; campesterol: 20%-40%; stigmasterol: 5%, referred to herein as sterols), or no additive as a control. All samples were tested in a mixed state without further aging or further aged in a pressure aging vessel (PAV) according to established aging conditions used in the paving industry (e.g., see ASTM D6521). Under unaged conditions (i.e., no further PAV aging) and after each aging cycle, high temperature PG grade results were determined using ASTM 7175 "Standard Test Method for Determining Rheological Properties of Asphalt Binders Using Dynamic Shear Rheometer", and the clinical T was obtained from the 4 mm dynamic shear rheometer data according to the test procedure developed by Sui et al.1. s临界 、T m临界and ΔTc. Asphaltenes were determined as n-heptane insolubles according to ASTM D3279. High temperature stiffness properties for all samples at all aging conditions were determined using ASTM D7175, and low temperature properties were determined using a 4 mm dynamic shear rheometer (DSR) procedure according to (Sui C, 2010), (Sui CF, 2011), (Farrar, 2012). Data analysis was performed using RHEA software (ABATECH, 2018), and the low temperature ultimate stiffness (S value) rating and low temperature ultimate relaxation (m value) rating of the asphalt after each aging step were determined using the 4 mm DSR geometry. These parameters will be referred to as TS critical and Tm critical, respectively. Based on these data, the parameter Delta Tc (ΔTc) was calculated as (TS critical - Tm critical), which is an industry adopted modification of the work reported by Anderson et al. (Anderson, 2011). IATROSCAN analysis and Fourier transform infrared spectroscopy (FTIR) data were collected for all samples at all aging conditions. IATROSCAN analysis was performed using an IATROSCAN TH-10 hydrocarbon analyzer using the procedure described in the following references: JF. Masson, T. Price, and P. Collins, “Dynamics of Bitumen Fractions by Thin-Layer Chromatography / Flame Ionization Detection,” Energy & Fuels 2001, 15, 955-960; Baumgardner, GL, Masson, JF, Hardee, JR, Menapace, AM and Williams, AG, 2005, Polyphosphoric acid modified asphalt: proposed mechanisms, Journal of the Association of Asphalt Paving Technologists, 74, pp. 283-305; Baumgardner, GL, 2015, Characterization and implementation of ground tire rubber as post-consumer polymers for asphalt concrete, Mississippi State University.Briefly, asphalt binders are deasphalted according to ASTM method D-3279 "Standard Test Method for n-heptane Insoluble Matter" to produce asphaltenes (A) (i.e., the n-heptane insoluble portion) and soft asphaltenes (resins (R), cyclic compounds (C), and saturates (S)) as the n-heptane soluble portion.

[0150] Spectral FTIR data were collected for all samples under all aging conditions. __________________ 1 Changping Sui et al.. "New Technique for Measuring Low-TemperatureProperties of Asphalt Binders with Small Amounts of Material." TransportationResearch Record.Transportation Research Board, Washington, DC, US, Vol.2179, 1December 2010, pages 23-28.

[0151] This example shows that sterols slow down or delay the aging rate of asphalt binders. This example also shows that asphalt binders containing sterols can be reused or regenerated to serve as sterols that delay aging.

[0152] Sterols were added to the laboratory aged adhesive at various levels (0, 0.5%, 2.5%, 5%, 7.5%, 10% and 12.5%) and each sample was aged for an additional 20, 40 and 60 hours in a pressure aging vessel (PAV) according to ASTM D6521. Fig.12 The asphaltene level of the 12.5% ​​sterol blend after 60 hours of aging is shown to be 34.9%, which is comparable to the asphaltene levels of the 0% and 0.5% blends after 20 hours of aging. This is equivalent to the 12.5% ​​asphalt being aged three times longer than the untreated sample. The asphaltene level of the 5% sterol sample after 40 hours of aging is 34.7%, which is comparable to the unaged sample after 20 hours of aging.

[0153] These samples were also evaluated by FTIR profiles of aged adhesives at different sterol levels in PAV for aging times ranging from 0 to 60 hours. Fig.13 and Fig.14 is the FTIR spectrum of pure phytosterols, showing the -1 Functionality-dependent wavenumber region. Fig.13 and Fig.14Shown are the regions of the spectrum used to quantify sterol functionality after blending with an adhesive followed by aging. Fig.15 Shown are the FTIR results of subtracting the 60 hour PAV spectrum of the control adhesive from the FTIR spectrum of the 60 hour 5% sterol blend. Fig.16 Shown are FTIR results of a 60 hour PAV of the control adhesive subtracted from the FTIR spectrum of a 50 / 50 blend of a 60 hour PAV without sterols and a 60 hour PAV of a 10% sterol blend in the same starting adhesive. Fig.15 and Fig.16 The FTIR spectrum in the -1 Up to 943cm -1 The sterol regions of the 247 genes are similar in appearance and quantity. Fig.15 The results in are for samples aged for 60 hours containing 5% sterols, while Fig.16 The results in are data for two equally combined 60 hour aged samples (one without sterols and one with 10% sterols). Fig.15 The data showed that the sterols in the 5% sterol sample were still present after aging for 60 hours, while Fig.16 The data show that when the 10% sterol sample is mixed with an equal amount of sterol-free asphalt, the results are similar to Fig.15 The only way this could happen is if the 10% sterol was not consumed during the aging of the 10% sterol adhesive. Fig.17 is used to get Fig.16 Subtraction spectrum results of a 10% sterol blend aged for 60 hours. Fig.17 Quantitative data in the sterol area ratio Fig.15 and Fig.16 This indicates that a full 10% of the sterols were present in the sample prior to blending with the 0% sterol sample. Example 5

[0154] Recycled sterols already present in aged asphalt binders were tested to determine if it could be used as a source of sterol additives to retard aging. 20 grams of a 60 hour PAV sample containing 10% sterols was blended with 20 grams of a 60 hour PAV sample of a control binder containing no sterols. This means that if none of the sterols were consumed, the final blend contained the theoretical amount of 5% sterols. If the assumption of no sterol loss holds true, the high and low temperature properties should be similar to the data for the 60 hour 5% sterol blend. Fig.18 The R-values ​​and low temperature data for 60 hour PAV aged samples of the aged base adhesive control, 5% and 10% sterols, and a 50 / 50 physical blend of 10% sterol and control are shown. For comparison, the numerical average of the data for the 10% sterol and control samples is also shown.Fig.18 The data in show that the numerical averages and data for the 50 / 50 physical blend are somewhat similar but not identical. The R-values ​​for the 5% sterol sample and the 50 / 50 physical blend are very close, while the numerical average is higher. This numerical average result means that the more severely aged the control, the R-value data for the 50 / 50 average blend will skew toward the R-value of the control adhesive. The same is true for the Tm critical data and the ΔTc data. The numerical average for the Tm critical is 2.5°C warmer than the 50 / 50 blend data. Since the Ts critical data for all samples are similar, the resulting ΔTc data shows that for the 50 / 50 physical blend, the numerical average is about 3°C ​​more negative than the ΔTc. Fig.19 The high temperature data shown in show that the numerical averages are biased toward the high temperature values ​​of the control, while the results for the 50 / 50 blend are within 1 °C of the original 5% sterol sample.

[0155] Fig. 20 Black space plots for several of the blends discussed above are shown. A Black plot is a graph of the complex modulus (G*) on a logarithmic scale as a function of the phase angle on a linear scale. This arrangement of plots is called "Black space". Fig. 20 Black plots are shown for an aged base control prior to any additional PAV aging and an aged base control after 60 hours of PAV aging. The data shows that at a stiffness of 1E7 Pascals, the phase angle has shifted from 38.7° for the unaged sample to 33.2° for the 60 hour PAV sample. The 10% sterol sample aged 60 hours has a slightly higher phase angle (about 40.3°) than the unaged control; this is another indicator of the sterols' aging-retarding benefit. Also shown are data for a 5% sterol sample aged 60 hours and a 50 / 50 blend of a 10% sterol sample and a control sample, both aged 60 hours. The Black spatial plots are on the same line, which means that according to Fig. 20 The data also show that the 10% sterols are present and viable in the 60 hour aged sample, so when blended with the 60 hour aged control, the phase angle shifts to a higher value consistent with the 5% sterol sample. Example 6

[0156] Additional experiments were conducted to demonstrate that the sterols were not consumed nor reacted with the asphalt. In this experiment, PG 64-22 binder was used as the base material. Blends of 6% and 12% in PG 64-22 were produced. All three binders were tested in unaged conditions and after aging for 60 hours in PAV.

[0157] An aging time of 60 hours in PAV was chosen because previous tests have shown a good linear relationship between PAV aging time and the resulting test properties, and furthermore, the purpose of this study was to demonstrate that after extended aging times, sterols are present in the aged adhesive and can be recovered and still be used as an anti-aging additive.

[0158] Additional blends produced were: a. PG 64-22 aged for 60 hours + 6% sterols added after comparison with PG 64-22 + 6% sterols aged for 60 hours b. PG 64-22 aged for 60 hours + 12% sterols added after comparison with PG 64-22 + 12% sterols aged for 60 hours c. 50% PG 64-22 (0% sterols) aged 60 hours + 50% PG 64-22 + 12% sterols aged 60 hours. This blend was compared to PG 64-22 + 6% sterols aged 60 hours.

[0159] If 60 hours of PAV does not consume sterols, then the performance of the 60 hour aged adhesive plus sterol blend should be similar to the PAV aged adhesive + post added new sterol. In addition, the performance of a 50 / 50 blend of aged materials used to produce a 6% sterol blend should be comparable to 60 hour aged PG 64-22 with 6% sterol post added.

[0160] All blends were tested for rheological properties to determine high and low temperature properties and to calculate the rheological index (R-value). Asphaltenes were determined using ASTM D1759 and the resulting soft asphaltene fraction was characterized using the IATROSCAN test procedure to determine saturates, cyclic compounds and resins and then calculate the colloidal index.

[0161] As an integral part of the IATROSCAN testing program, it was determined that sterols become part of the resin fraction, just like most bio-derived regeneration and softening additives. However, unlike bio-derived additives, sterols appear as a separate peak within the resin elution region. This peak is present in unaged as well as aged adhesives and can be quantified by integrating the sterol region separately from the remaining resin region.

[0162] Black space plots were generated to compare the log G* as a function of phase angle for the various blends described above. The Black space plots show that the PG 64-22 + 12% sterol blend aged for 60 hours follows the same data trajectory as the PG 64-22 + 12% sterol added after aging for 60 hours. In addition, the Black space plots of the pre-aged or aged adhesive plus post-added 64-22 blends, or the 50 / 50 blends of the aged adhesive and the aged adhesive plus 12% sterol to produce the 6% blend all follow the same Black space data plot. The test performance of the above blends is shown in the figures discussed below.

[0163] Fig.21 and Fig. 22 The high temperature PG ratings of adhesives at 1 kPa stiffness are shown for PG 64-22 + 0% sterol, PG 64-22 + 6% sterol, and PG 64-22 + 12% sterol. Fig.21 ) and high temperature grades at 2.2 kPa stiffness ( Fig. 22 ). Both figures also show the high temperature PG grade of the above blends after 60 hours of PAV aging.

[0164] Fig.23 The low temperature creep critical properties (Tm Critical) are shown for the same blends as above. The low temperature stiffness properties (TS Critical) show similar properties, but since Tm Critical controls the low temperature PG rating of the adhesive, except for the unaged adhesive samples, it is the important property.

[0165] Fig.24 A graph of R-value data for unaged and aged blends with and without sterols is shown. As the adhesive ages, the R-value increases, indicating a decrease in the flexibility of the adhesive. Fig.23 A comparative examination of the Tm critical plots in shows that the sample with the lowest critical temperature (i.e., the best ability to relieve low-temperature thermal stress) is Fig.24 The sample with the lowest R value. Fig.24 It also shows that the R-values ​​for both unaged and aged conditions decrease as the sterols are increased from 0% to 6% to 12%. Furthermore, whether the sterols are post-added to the aged adhesive or pre-added and then aged, or the two aged adhesives are blended to produce a final sterol concentration of 6%, the R-values ​​for the blends resulting in 6% sterol content are within 0.1 units. The two 12% samples, post-added and pre-added and aged, have the same R-values.

[0166] Fig.25Asphaltene content of different adhesives as a function of aging is shown. The unaged adhesive shows only a small change in asphaltene due to the addition of sterols. Even in the case of 12% sterols, the reduction in asphaltene is 1.7%. The difference is more obvious after aging. Adding 6% sterols only reduces the accumulation of asphaltene by 1% to 1.6%, and adding 12% reduces the accumulation of asphaltene by 3.7% to 4.4%. The blends in which sterols are added to PG 64-22 aged for 60 hours PAV have lower asphaltene than the blends in which sterols are added beforehand and then aged. This indicates that post-addition of sterols is slightly more effective in destroying adhesive aging compared to pre-addition and aging. However, the 50 / 50 blend of aged 64-22 and aged 64-22 + 12% sterols produces results very close to the 6% pre-blended and aged samples. These data are all similar, reflecting the presence of similar amounts of active sterols in the samples.

[0167] Figure 26 to Figure 28 A Black space plot of the results for the generated samples is shown. Fig.26 The following are graphs of all blends of PG 64-22 with 0%, 6%, and 12% sterols, unaged and aged, and the various blends described. The main point is that the 60 hour PAV of 64-22 + 12% is plotted highest on the graph, indicating that this sample has the highest phase angle for any given complex shear modulus value. The higher the phase angle for a given modulus, the more flexible the adhesive is. PG 64-22 + 6% sterols is second and the 0% sterol blend is third. PG 64-22 + 0% sterol aged for 60 hours is lowest. For two samples, there are 3 graphs of 12% sterol aged for 60 hours. One sample was tested twice and the results of both tests are plotted. The 60 hour PAV of the sample aged with 12% sterol pre-added and the 60 hour PAV of the undoped PG 64-22 with 12% sterol post-added are plotted on the same Black space line, supporting the conclusion that the sterol performance is not degraded by aging. The Black space plot for blends containing 6% sterols supports the same conclusion. Multiple runs were performed on the following blends: 6% blends pre-added then recycled sterol blend, blends with 6% sterols post-added to PG 64-22 (unadulterated) aged 60 hours, PG 64-22 (unadulterated) aged 60 hours, and a 50 / 50 blend of 64-22 + 12% sterols aged 60 hours. All of these data were plotted on the same Black space line.

[0168] Fig. 27 Overlaid are the images of the aged 6% sterols only sample. Fig.28 The graph is of only the aged 12% sterol sample to make it easier to visualize the data. Analysis of IATROSCAN data of PG 64-22 aged with 0%, 6% and 12% sterols

[0169] As the asphalt binder ages, the asphaltenes increase, e.g. Fig.25 The data in the graphs have demonstrated this. The material remaining after the removal of the asphaltenes is called the soft asphaltene fraction, which consists of three general fractions that are characterized by their relative solubility and can be separated by chromatography. These fractions are saturates or paraffinic compounds that are soluble in n-pentane, cyclic compounds or aromatic compounds that are soluble in a blend of toluene and chloroform, and resins that are almost insoluble in a blend of toluene and chloroform. With aging, the concentration of saturates changes little, the concentration of cyclic compounds decreases, and the concentration of resins increases. Fig.29 The graph shows that the volume of cyclic compounds decreased, the volume of resins increased, and the volume of saturates remained relatively similar. Also, the inset label in the graph shows that the asphaltenes doubled.

[0170] When sterols are added to an asphalt binder (PG 64-22 in this case), the sterols elute in the resin fraction. All other bio-derived additives have been studied for elution as resins, even though they are not molecularly identical to the asphalt resins. These bio-based materials are not soluble in n-pentane or toluene and are only slightly soluble in chloroform. Fig.30 A typical IATROSCAN data plot is shown for 12% sterol post added to PG 64-22 aged in PAV for 60 hours. Although the sterol was post added, it still appears as a separate peak in the resin fraction. Fig.31 It shows that it makes no difference whether the sterols are pre- or post-added, the chromatograms are identical with only slight differences in elution times. These peak areas are not quantitative because Fig.31 In the case of , they will produce a value of 12.0. Each sample was spotted on 5 silica treated rods and 5 GC-FID scans were collected. There are differences in elution amounts and the data plots show that the sterol areas are adjacent to the main resin peak, so the sterol amounts will vary somewhat from test to test. Fig.31 , similar areas are shown, but neither is 12.0%; importantly the similarity in area indicates that the sterol levels in both samples are the same, whether post-added after aging of the base binder or pre-added before aging.

[0171] Fig.32 The data plots for 64-22 with 6% sterols are shown. One sample is for unaged PG 64-22 + 6% sterols and two data plots are for PG 64-22 + 6% sterols followed by 60 hours PAV aging. The asphaltene content adjusted (normalized) areas for these samples are shown as 7.3, 6.4, and 6.9. Again, as explained above, these are not exactly 6% and would not be expected to be 6%. Double Check Fig.32, showing that the sterol peak of the unaged sample is smaller than that of the aged sample. Since the unaged sample is unaged, the resin area is reduced compared to the resin area of ​​the aged sample, and the area of ​​each corresponding peak is normalized to the total area of ​​100%; therefore, when adjusted for the sterol content of the unaged adhesive, the relative value of the sterol peak in the unaged sample relative to the other components is 7.3.

[0172] Fig.33 A single data plot is shown for the blend addition of 50% PG 64-22 aged 60 hours without sterols and 50% PG 64-22 + 12% sterols aged 60 hours. When normalized for asphaltene content, the blend averaged 6% and the area for this sample was calculated to be 6.3. Example 7

[0173] A base 64-22 adhesive will be used, blended with 0%, 5%, and 10% sterols in unaged conditions and after aging for 60 hours in PAV. These samples will be compared to 60 hour PAV samples that already contain 10% sterols and blended with the original oxidized adhesive that does not contain sterols. Various parameters such as R values, Tm critical, Ts critical data, and ΔTc data will be determined. The samples are also evaluated in the Black space diagram as described above.

[0174] Although specific embodiments have been illustrated and described herein for the purpose of describing preferred embodiments, it will be understood by those skilled in the art that a variety of alternative or equivalent embodiments made to achieve the same purpose may replace the specific embodiments shown and described without departing from the scope of the present invention. This application is intended to cover any modifications or variations of the preferred embodiments discussed herein. Therefore, it is apparent that the present invention is limited only by the claims and their equivalents.

[0175] Those of ordinary skill in the relevant art will recognize that the subject matter herein may include fewer features than shown in any individual embodiment described above. The embodiments described herein are not meant to be an exhaustive presentation of the ways in which the various features of the subject matter thereof may be combined. Thus, the embodiments are not mutually exclusive combinations of features; rather, as will be appreciated by those of ordinary skill in the art, the various embodiments may include combinations of different individual features selected from different individual embodiments. Furthermore, unless otherwise stated, elements described with respect to one embodiment may be implemented in other embodiments, even when not described in these embodiments.

[0176] Although a dependent claim in the claims may refer to a specific combination of one or more other claims, other embodiments may also include a combination of a dependent claim with the subject matter of each other dependent claim or a combination of one or more features with other dependent or independent claims. Unless it is stated that a specific combination is not intended, such combination is herein proposed.

[0177] Any incorporation by reference of the above documents is limited such that no subject matter is incorporated that is contrary to the explicit disclosure herein. Any incorporation by reference of the above documents is further limited such that no claims included in these documents are incorporated herein by reference. Any incorporation by reference of the above documents is further limited such that any definitions provided in the documents are not incorporated herein by reference unless expressly included herein.

[0178] The published patent applications having publication numbers US20160362338, WO2017027096, WO2017213692, WO2017213693, WO2018031540, US20180215919, WO2018144731 and WO2019023172 are incorporated herein by reference for all purposes.

Claims

1. A method for delaying the aging rate of an asphalt-based roofing material, the method comprising: The original asphalt binder composition is air-blown to provide an oxidized original asphalt binder composition, sterol is added to the oxidized original asphalt binder composition, and, after the addition of the sterol, the oxidized original asphalt binder composition is used to manufacture the asphalt-based roofing material.

2. A method for manufacturing a roofing material, comprising: treating the virgin asphalt binder to provide an oxidized virgin asphalt binder; adding sterols to the oxidized raw asphalt binder composition to form a coating asphalt composition; as well as A roofing material substrate is coated with a coating asphalt binder composition.

3. The method according to claim 1 or 2, characterized in that: The roofing material includes roofing tiles, roofing rolls or combined roofing materials.

4. The method according to claim 1 or 2, characterized in that: The oxidized virgin asphalt binder includes virgin asphalt binder that meets ASTM specification D312 for Type II, Type III, and Type IV.

5. The method according to claim 1 or 2, characterized in that: The sterols include recycled sterols.

6. The method according to claim 1 or 2, characterized in that: The coating asphalt binder may also contain fillers, aggregates, or both.

7. The method according to claim 6, characterized in that The filler material includes sedimentary rock particles.

8. The method according to claim 6, characterized in that The filler includes limestone particles.

9. The method according to claim 6, characterized in that The aggregate includes slate, basalt, nepheline, or a combination thereof.

10. The method according to claim 1 or 2, characterized in that: The sterols include recycled sterols, neosterols or a combination thereof.

11. The method according to claim 1 or 2, characterized in that: The sterols are phytosterols.

12. The method according to claim 1 or 2, characterized in that: The sterols are phytostanols.

13. The method according to claim 1 or 2, characterized in that: The sterol is cholesterol.

14. The method according to claim 1 or 2, characterized in that: The sterols are pure sterols.

15. The method according to claim 1 or 2, characterized in that: The sterols are crude sterols.

16. The method according to claim 15, characterized in that The crude sterols are bioderived or are distillation residues of a bioderived origin.

17. The method according to claim 15, characterized in that The crude sterols include tall oil pitch.

18. The method according to claim 15, characterized in that The crude sterols include soybean oil.

19. The method according to claim 15, characterized in that The crude sterols include corn oil.

20. The method according to claim 1 or 2, characterized in that: The sterols are a combination of pure sterols and crude sterols.

21. The method according to claim 20, characterized in that The weight ratio of the pure sterols to the crude sterols of the combination is from 10:90 to 90:

10.

22. The method according to claim 1 or 2, characterized in that The sterol is present in an amount of 1 wt.% to 10 wt.% based on the weight of the asphalt binder.

23. The method according to claim 1 or 2, characterized in that The sterol is present in an amount of 1 wt.% to 3 wt.% based on the weight of the asphalt binder.

24. The method according to claim 2, characterized in that The roofing material substrate comprises felt or mesh.

25. The method according to claim 2, characterized in that The roofing material substrate includes glass fiber or cellulose fiber mat.

26. The method according to claim 2, characterized in that The coating step includes coating at least a portion of a top portion of the substrate.

27. The method according to claim 2, characterized in that The coating step includes coating at least a portion of a bottom portion of the substrate, or portions of a top and bottom portion of the substrate.

28. The method according to claim 2, characterized in that Coating the roofing material substrate includes saturating the substrate.

29. The method according to claim 1, characterized in that The oxidized virgin asphalt binder provides a ΔTc value that is 2° C. to 5° C. higher than the oxidized virgin asphalt binder without sterols.

30. The method according to claim 1 or 2, characterized in that The oxidized virgin asphalt binder composition provides a ΔTc value that is 2° C. to 5° C. higher than the oxidized virgin asphalt binder without the sterol after 40 hours of PAV aging.

31. The method according to claim 1 or 2, characterized in that: The sterol is included in an amount effective to provide a less negative ΔTc value after aging.

32. The method according to claim 1 or 2, characterized in that The sterol is included in an amount effective to cause the ΔTc value of the aged asphalt binder composition to be less negative than a similarly aged asphalt binder composition containing the crude sterol.

33. A roofing material comprising a coated roofing substrate, wherein the coated roofing substrate includes a coating comprising an asphalt binder composition, the asphalt binder composition comprising sterols and an oxidized virgin asphalt binder, wherein the oxidized virgin asphalt binder comprises an air blown virgin asphalt binder.

34. The roofing material according to claim 33, characterized in that The coating asphalt binder composition also includes fillers, pellets, or both.

35. The roofing material according to claim 34, characterized in that The filler material includes sedimentary rock particles.

36. The roofing material according to claim 34, characterized in that The filler includes limestone particles.

37. The roofing material according to any one of claims 34 to 36, characterized in that The granular material comprises slate, basalt or nepheline.

38. The roofing material according to any one of claims 33 to 36, characterized in that The roofing substrate comprises felt or mesh.

39. The roofing material according to any one of claims 33 to 36, characterized in that The roofing substrate includes fiberglass or cellulose mat.

40. The roofing material according to any one of claims 33 to 36, characterized in that The roofing material includes roofing tiles, roofing rolls or composite roofing.

41. The roofing material according to any one of claims 33 to 36, characterized in that The oxidized virgin asphalt binder includes virgin asphalt binder that meets ASTM specification D312 for Type II, Type III, and Type IV.

42. The roofing material according to any one of claims 33 to 36, characterized in that The sterols include recycled sterols, neosterols or a combination thereof.

43. The roofing material according to any one of claims 33 to 36, characterized in that The sterols are phytosterols.

44. The roofing material according to any one of claims 33 to 36, characterized in that The sterols are phytostanols.

45. The roofing material according to any one of claims 33 to 36, characterized in that The sterol is cholesterol.

46. ​​The roofing material according to any one of claims 33 to 36, characterized in that The sterols are pure sterols.

47. The roofing material according to any one of claims 33 to 36, characterized in that The sterols are crude sterols.

48. The roofing material according to claim 47, characterized in that The crude sterols are of biologically derived origin or distillation residues of biologically derived origin.

49. The roofing material according to claim 47, characterized in that Crude sterol sources include tall oil pitch.

50. The roofing material according to claim 47, characterized in that The crude sterols include soybean oil.

51. The roofing material according to claim 47, characterized in that The crude sterols include corn oil.

52. The roofing material according to any one of claims 33 to 36, characterized in that The sterols are a combination of pure sterols and crude sterols.

53. The roofing material according to claim 52, characterized in that The weight ratio of the pure sterols to the crude sterols of the combination is from 10:90 to 90:

10.

54. The roofing material according to any one of claims 33 to 36, characterized in that The sterol is present in an amount of 1 wt.% to 10 wt.% based on the weight of the asphalt binder.

55. The roofing material according to any one of claims 33 to 36, characterized in that The sterol is present in an amount of 1 wt.% to 3 wt.% based on the weight of the asphalt binder.

56. The roofing material according to any one of claims 33 to 36, characterized in that The coating coats at least a portion of a top portion of the roofing material substrate.

57. The roofing material according to any one of claims 33 to 36, characterized in that The coating coats at least a portion of the bottom of the roofing material substrate, or portions of the top and bottom of the roofing material substrate.

58. The roofing material according to any one of claims 33 to 36, characterized in that The coating penetrates the roofing material substrate.

59. The roofing material according to any one of claims 33 to 36, characterized in that The asphalt binder composition provides a ΔTc value that is 2° C. to 5° C. higher than an asphalt binder composition that does not contain sterol.

60. The roofing material according to any one of claims 33 to 36, characterized in that The asphalt binder composition provides a ΔTc value that is 2° C. to 5° C. higher than an asphalt binder without sterol after 40 hours PAV aging.

61. The roofing material according to any one of claims 33 to 36, characterized in that The sterol is included in an amount effective to provide a less negative ΔTc value after aging.

62. The roofing material according to any one of claims 33 to 36, characterized in that The sterol is included in an amount effective to cause the ΔTc value of the aged asphalt binder composition to be less negative than a similarly aged asphalt binder containing the crude sterol.

63. A roof comprising the roofing material according to any one of claims 33 to 62.

Citation Information

Patent Citations

  • Use of sterols as an additive in asphalt binder

    US20160362338A1

  • Sterol additive in asphalt pavement

    US20180215919A1

  • Production of sterols from tall oil pitch

    US2715638A

  • Emulsion containing a plant extract, method for producing said emulsion and for obtaining a plant extract

    WO2001072315A1

  • Device and method for continuously extracting extract materials from solid materials, for washing solid materials and recrystallizing

    WO2004016336A1